Legacy Beliefs Across Generations: Comparing Views of Older Parents and Their Adult Children. (March 2019) - Meuser, Thomas M.; Mthembu, Thuli G.; Overton, Brianne L.; Roman, Nicolette V.; Miller, Rebecca D.; Lyons, Katharina P.; Carpenter, Brian D.
This mixed-methods study examined legacy beliefs (i.e., anticipated remembrances and linkages to the self after death) as understood in 14 older parent and adult child pairs. This work validates and expands on a 2005 typology of legacy beliefs from gerontologists, Elizabeth Hunter and Graham Rowles. A structured interview was administered separately to parents and children, coded for legacy examples (i.e., those unique to the parent, overlapping, unique to the child), and analyzed with respect to expectations of similarity reported by each participant. Most predicted moderate to high overlap in mutual understanding of parent legacy. This was not the case, as there were far more unique legacy examples given than shared. Pairs agreed least with respect to material legacies, with half showing no agreement. All reported finding the structured discussion of legacy to be beneficial, with some indicating an intention to continue these discussions further. This work may constitute a new approach to intervention.